Nature versus nurture in heat stress induced learning between inbred and outbred populations of Lymnaea stagnalis. (January 2022) - Rivi, Veronica; Batabyal, Anuradha; Benatti, Cristina; Blom, Johanna MC.; Lukowiak, Ken
Abstract: Changing environmental conditions often lead to microevolution of traits that are adaptive under the current selection pressure. Currently, one of the major selection pressures is the rise in temperatures globally that has a severe impact on the behavioral ecology of animals. However, the role of thermal stress on neuronal plasticity and memory formation is not well understood. Thermal tolerance and sensitivity to heat stress show variation across populations of the same species experiencing different thermal regimes. We used two populations of the pond snail Lymnaea stagnalis : one lab-bred W-snails and the other wild Delta snails to test heat shock induced learning and memory formation for the Garcia effect learning paradigm. In Garcia effect, a single pairing of a heat stressor (30 °C for 1h) with a novel taste results in a taste-specific negative hedonic shift lasting 24h as long-term memory (LTM) in lab bred W-snails. In this study we used a repeated heat stress procedure to test for increased or decreased sensitivity to the heat before testing for the Garcia effect. We found that lab-bred W-snails show increased sensitivity to heat stress after repeated heat exposure for 7days, leading to enhanced LTM for Garcia effect with only 15min of heat exposure instead of standard 1h. Surprisingly, the freshly collected wild snails do not show Garcia effect. Additionally, F1 generation of wild snails raised and maintained under laboratory conditions still retain their heat stress tolerance similar to their parents and do not show a Garcia effect under standard learning paradigm or even after repeated heat stressor. Thus, we found a differential effect of heat stress on memory formation in wild and lab bred snails. Most interestingly we also show that local environmental (temperature) conditions for one generation is not enough to alter thermal sensitivity in a wild population of L. stagnalis . Highlights: Environmental changes shift adaptive traits in animals. Heat stress response is different between lab and wild snails. Raising wild snails under lab conditions do not shift their response. Heat tolerance in wild is an evolved adaptive trait.